Literary Neuroexistentialism: Coming to Terms with Materialism and Finding Meaning in the Age of Neuroscience through Literature - Høeg, ML (Springer, 2024)
With the rise of the scientific authority of neuroscience and recent neurotechnological advances, the understanding of the human being and its future is beginning to undergo a radical change. As a result, a normative and existential vacuum is opening and hopes as well as fears about the future are flourishing. Some philosophers are anticipating a broad neuroscientific disenchantment, sociocultural disruption and a new existential anxiety related to the clash of the neuroscientific and humanistic image of humans. Others are expecting the technological and scientific developments to lead to human enhancement and existential emancipation. In the first part of this commentary, I outline these two contrasting responses to the rise of neurocentricism and non-anthropocentrism. In the second part, I argue that the divide between the old anthropocentric paradigm and the emerging neuroscientific is misconceived and that literature and fictional narrative are particularly illustrative of the possibility of integrating scientific materialism with humanism. I use the contemporary literary-philosophical work The Creative Act by Rick Rubin to show that humanist ideas can indeed cohere with anti-essentialist and neuroscientific notions of personal identity and self and how existential meaning and comfort can be found in a neuroscientifically and deterministically explained world.